A MÁQUINA FABULATÓRIA DA MÍDIA E O RE-ENCANTAMENTO DA POLÍTICA: A ESTRUTURA MÍTICA DAS CAMPANHAS ELEITORAIS MAJORITÁRIAS - Vasconcelos Accioly Carvalho, Rejane (Caderno CRH, 2007)
O objetivo central do texto é abordar as conexões entre política e estrutura das narrativas míticas nas condições de vigência de uma cultura e sociabilidade vigorosamente mediatizadas. A hipótese central é que a máquina enunciativa da mídia opera cada vez mais pelo aciconamento da dimensão fabulosa e fabulatória do imaginário popular e não por um ideal de objetividade de reportar-se apenas a fatos e acontecimentos que lhe são exteriores. A tendência de re-encantamento do mundo pela exarcebação do nosso tráfico com as imagens contraria, assim, a famosa tese de Weber do desencantamento do mundo moderno pela técnica. As campanhas políticas majoritárias são tomadas como momentos privilegiados de investimento simbólico forte e portanto mítico, na construção das imagens públicas dos protagonistas que se colocam no centro da disputa pelo voto. The Fabulatory Machine of the Media and the Re-enchantment of politics: The Mythical Structure of Electoral Campaigns Rejane Vasconcelos Accioly Carvalho The central aim of the text is to tackle the connections between politics and the structure of mythical narratives in which a vigorously mediatized culture and sociability are in force. The central hypothesis is that the enunciative machine of the media operates more and more through the activation of the fabulous and fabulatory dimension of the popular consciousness and not through an ideal of objectivity in which only the facts and events which are exterior to it are reported. The tendency towards a re-enchantment of the world through the amplification of our exchange of images would oppose in this way Weber's famous thesis of the disenchantment of the modern world by technicism. Political campaigns are taken as moments privileged by strong symbolic investment and therefore mythical, in the construction of the public images of the protagonists that place themselves in the centre of the dispute for votes. The campaign of Tasso Jereissati for the government of the State of Ceará in 1986 is analysed as a model example of the approximation of politics to fabulous narratives concerning the confrontation of the forces of good and evil, in which everybody can participate thanks to the media. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br